3,5-Bis(4-methoxyphenyl)-4H-1,2,4-triazol-4-amine - Yang, Hui; Huang, Zhan-Dong; Yang, Guang; Ng, Seik Weng (International Union of Crystallography, 2010)
The title compound, C16H16N4O2, crystallizes with two molecules in the asymmetric unit, which are related by a non-crystallographic centre of inversion. The phenylene rings are twisted out of the mean plane of the triazole ring by 19.3 (1) and 21.4 (1)° for one independent molecule and by 16.3 (1) and 18.1 (1)° for the other molecule. In the crystal, adjacent molecules are linked by amine-triazole N-H...N hydrogen bonds, forming chains running along the a axis.